2020
DOI: 10.1002/uog.22145
|View full text |Cite|
|
Sign up to set email alerts
|

ISUOG Practice Guidelines (updated): sonographic examination of the fetal central nervous system. Part 1: performance of screening examination and indications for targeted neurosonography

Abstract: ISUOG Practice Guidelines (updated): sonographic examination of the fetal central nervous system. Part 1: performance of screening examination and indications for targeted neurosonography Clinical Standards Committee The International Society of Ultrasound in Obstetrics and Gynecology (ISUOG) is a scientific organization that encourages sound clinical practice, and high-quality teaching and research related to diagnostic imaging in women's healthcare. The ISUOG Clinical Standards Committee (CSC) has a remit to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
227
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(235 citation statements)
references
References 41 publications
1
227
0
7
Order By: Relevance
“…We congratulate the authors of the recent Guideline on sonographic examination of the fetal central nervous system (CNS) 1 for their concise and cogent work, most particularly for their attention to the scanning of the fetal spine. However, we would like to offer some comments.…”
mentioning
confidence: 99%
“…We congratulate the authors of the recent Guideline on sonographic examination of the fetal central nervous system (CNS) 1 for their concise and cogent work, most particularly for their attention to the scanning of the fetal spine. However, we would like to offer some comments.…”
mentioning
confidence: 99%
“…Second, the authors found that the accuracy of the neurosonogram was not influenced by cephalic or breech fetal position, thus speculating on the usefulness of transvaginal ultrasound in cases of cephalic position. However, ISUOG guidelines on sonographic examination of the fetal central nervous system report that ‘vaginal probes have the advantage of operating at a higher frequency than do abdominal probes and therefore allow a greater definition of anatomical details’ and provide a satisfactory assessment of the fetal brain from the end of the first trimester 2 , such that even an external cephalic version might be reasonable when evaluating some breech presenting fetuses 6 .…”
mentioning
confidence: 99%
“…By no means, though, do we argue that there is no role at all for fetal MRI. We strongly endorse the 2020 International Society of Ultrasound in Obstetrics and Gynecology (ISUOG) updated neurosonography guidelines 2 , which state that ‘it is not appropriate to request MRI based only on suspicion of brain abnormality raised at screening ultrasound’. This is comparable to the 2017 ISUOG fetal MRI guidelines 3 , stating that a basic (screening) brain examination is insufficient prior to requesting MRI.…”
mentioning
confidence: 99%